KERJASAMA INDONESIA-JEPANG DALAM PROGRAM MANUFACTURING INDUSTRY DEVELOPMENT CENTER (MIDEC) PADA SEKTOR TEKSTIL TAHUN 2008-2013 - Michelle Maidangkay (2020)
The Manufacturing Industrial Development Center (MIDEC) is an organization that is part of the Indonesia, Japan Economic Partnership Agreement (IJEPA) Implementation Team in the industrial field. The collaboration which is based on the Minister of Industry Regulation Number: 77 / M-IND / PER / 9/2007 is tasked with carrying out economic cooperation between Indonesia and Japan in the development of the manufacturing industry as well as coordinating planning, implementation, monitoring and evaluation. MIDEC was formed as a driver of industrial capacity building to improve competitiveness in Indonesia's industrial sector. MIDEC covers 13 fields, one of which is the textile sub-sector. In Indonesia, this study found that an increase in textile exports, from Indonesia to Japan after the implementation of MIDEC programs such as basic studies, technical assistance / Dispatching Expert, seminars and workshops. This study will answer the research question of how the cooperation between Indonesia and Japan in the textile sector MIDEC because the textile sector is one of the driving sectors of the Indonesian economy with higher opportunities so that the impact on the amount of textile exports, from Indonesia to Japan continues to experience a significant increase and can be said to be successful increase exports of Indonesian textile products to Japan during 2008-2013. At the beginning of this research, discussion will be discussed about the background of the formation of MIDEC which originated from IJEPA, then describes MIDEC programs in the field of textiles as well as the implementation of the program and IJEPA policies that also help increase textile exports and how the impacts and obstacles in this bilateral cooperation. The results of this research are MIDEC activities such as seminars, workshops, visits to the Japanese and Indonesian textile industries, and sending experts. This study uses a qualitative approach with a case study method, namely the textile sector, which explains how the implementation of the MIDEC program resulted in an increase in textile exports from Indonesia to Japan.